A Bibliometric Analysis of out of School Learning Environments: Science Mapping - Fatih Seker; Muhammed Dogukan Balcin (Journal of Education in Science, Environment and Health)
The aim of this study is to understand and analyze the status, development and current trends of out-of-school learning by evaluating scientific studies published in the field of out-of-school learning environments in terms of various parameters. The bibliometric analysis method and Web of Science (WoS) database were used to carry out the research and achieve the determined goals. The research was limited to the years 1982-2021 and 3101 studies were evaluated. In this study scientific studies published on out-of-school learning were examined within the framework of the annual number of publications, keyword analysis, citation analysis, active researchers, journals and countries. In the results of the study, it was determined that the publication trend about out-of-school learning started in 2008 and has continued until today, with the most references occurring in the last 10 years. In addition, it was determined that the most cited author was “Nada Dabbagh”, the co-author was “Micheal Eraut”, the active journal was “Educational Technology & Society”, the most cited and co-cited journal was “Computer & Education” and the active collaborator country was “United States”. In this context, it is recommended that researchers increase their studies depending on needs. Furthermore, with the disappearance of the effects of the Covid19 epidemic over time, it is thought that many studies can be conducted in out-of-school learning environments.